The theory & practice of learning - Jarvis, Peter, 1937- (Kogan Page, 2003)
Learning is among the most basic of human activities. The study of learning, and research into learning is becoming a central part of educational studies. This is a comprehensive introduction to contemporary theories and modern practices of learning. Updated and expanded, this second edition should be of interest to teachers, facilitators, human resource developers and students of education. The contents cover: lifelong learning; the social background to learning; cognitivist theory; types of learning; learning using ICT; and philosophical reflections on learning.